(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Rheumatoid arthritis is a most common persistent inflammatory arthritis of unknown etiology marked by symmetric, peripheral poly arthritis and often result in joint damage and physical disability. Arthritis is always associated with arthralgia. It is 1.0-1.5% with a female to male ratio of 3:1 functional capacity decrease most rapidly at the beginning of disease and the function state of patients in their first year. R.A. Etiology like Immunological factor (HLA-DRB1), Hormonal factor, contraceptives pills, is also associated with a worse disease outcome in R.A. Particularly in genetically predisposed individuals, some environmental antigen trigger, probably a virus, stimulates the production of autoantibodies (IgM rheumatoid factor) against the body, own IgM immunologlobins. This process can become self perpetuating. The prominent feature is the formation of immune complexes. within the joint resulting from tissue damage. These complex activate complement and attract neutrophils. Phagocytosis of immune complexes by neutrophils leads to release of chemical mediators of inflammation. Continued inflammation stimulates the formation of a proliferative synovitis. This hypertrophic granulation tissue is called pannus. This process is responsible for the causing joint erosions. In Ayurveda it is clinically correlated with Aamvata. According to Bhavprakash Beautiful composition is given in Aamvata chikitsa 26th chapter Rasonadi Kwath. Conceptually it is play very effective role because of its Sothhara, Vedna-sthapana, Kapha-vatashamak, Deepan-Pachan, Anuloman, Shoola-prashman, and also Shunthi is Uttam Aama pachak. The aim of this article is to provide a management for RA by Rasonadi Kwath.